2006
DOI: 10.1089/mdr.2006.12.121
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Sequence Typing of Hospital-Associated Enterococcus faecium from Brazil Reveals Their Unique Evolutionary History

Abstract: We studied the genetic relationships between vancomycin-susceptible (n = 11) and -resistant Enterococcus faecium (VRE, n = 20) recovered from Brazil using a multilocus sequence typing (MLST) scheme. Grouping of allelic profiles revealed six clusters of related sequence types (STs) that differ in no more than two of the seven alleles. Of these, one cluster harbored 16 of the 20 isolates recovered during the first VRE outbreak in Brazil. The ampicillin and gentamicin resistance profiles were stable in the isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Of note, all VREfm isolated in this study were resistant to both ampicillin and quinolones, showing the same antimicrobial resistance profile observed for E. faecium of CC-17. Nevertheless, molecular epidemiological studies conducted with Brazilian E. faecium isolates from several hospitals showed that this complex is not common in our country 27,28 .…”
Section: Conflict Of Interest Financial Support Referencesmentioning
confidence: 70%
“…Of note, all VREfm isolated in this study were resistant to both ampicillin and quinolones, showing the same antimicrobial resistance profile observed for E. faecium of CC-17. Nevertheless, molecular epidemiological studies conducted with Brazilian E. faecium isolates from several hospitals showed that this complex is not common in our country 27,28 .…”
Section: Conflict Of Interest Financial Support Referencesmentioning
confidence: 70%
“…Molecular epidemiological studies have shown that the incidence of outbreaks caused by VRE fm strains in Brazil is not as high as in European countries and in the United States [25,35,45]. Palazzo et al (2011) [35] revealed that VRE fm outbreaks in Brazil are caused by strains that do not share a common evolutionary history.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, vancomycin-resistant Enterococcus faecium and E. faecalis are disseminated in hospitals in different regions 2,3 . Recognition of colonized patients represents a crucial step in controlling the dissemination of these organisms and is a laboratorybased strategy 4 .…”
Section: Introductionmentioning
confidence: 99%